Assessment on Traffic Noise Pollution in Malaysia - Azlina, Ismail; Intan Suhana, Mohd Razelan; Mohammad Amirulkhairi, Zubir; Mohd Faizal, Md Jaafar (Penerbit Universiti Malaysia Pahang, 2018)
The transportation system and its technology in Malaysia continues to evolve over time to meet the challenges towards fulfilling the aspirations of the people. The rapid development in the transportation system is of concern due to its significant effects on the environment and human health. Almost all human activities including traffic and transportation contribute to pollution such as noise and it has become an inevitable issue.